Making Employees Work in Spare Time as a Result of Computer Mediated Communication - Wróbel, Wróbel (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The goal of the article includes analysis of the phenomenon of organisations stimulating its employees to work in spare time as a result of Computer Mediated Communication: scale and scope, mechanisms and results. The scale of the phenomenon in researched companies was significant, the scope in terms of employees groups was diversified. In both organisations the phenomenon was the result of internal processes and clients’ pressure. Researched employees emphasized negative consequences (stress, family tensions) and in the same time they agreed they have got accustomed to work in a spare time.